2005
DOI: 10.1111/j.0022-1112.2005.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular matrix of Gadus morhua muscle contains types III, V, VI and IV collagens in addition to type I

Abstract: Confocal microscopy and immuno-histochemistry were used to examine collagens in the extracellular matrix of cod Gadus morhua swimming muscle. In addition to the well known presence of type I fibrous collagen, types III and VI were also found in the myocommata and the endomysium. The beaded collagen, type VI, was found in the endomysium and the network forming collagen, type IV, was found in the basement membrane. This is the first report of type V collagen in cod muscle and of types II, IV and VI in the muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
(20 reference statements)
1
16
0
Order By: Relevance
“…Collagen I was previously reported to be a major collagen of fish muscle, along with collagen V [26,27]. In our study collagen I epitopes were expressed throughout the ECM in a similar manner as lumican.…”
Section: Discussionsupporting
confidence: 70%
“…Collagen I was previously reported to be a major collagen of fish muscle, along with collagen V [26,27]. In our study collagen I epitopes were expressed throughout the ECM in a similar manner as lumican.…”
Section: Discussionsupporting
confidence: 70%
“…The pure components, collagen I and C‐4‐S, are chosen because other studies have shown that collagen I is the main collagen in the connective tissue in fish and C‐4‐S is the most prominent GAG present in the connective tissue in cod . The FTIR second derivative spectrum of commercial pure component collagen type I shows the strongest bands at amide I (1585‐1720 cm −1 ) and amide II (1500‐1586 cm −1 ) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Several types of collagen are the main constituents of connective tissue and they all contain a characteristic three polypeptide chain, which forms into a unique triple helical structure . Collagen determines the connective tissue strength and structure , and the most abundant collagen type in fish muscle is the fibrillar collagen type I . PGs are complex and multifunctional molecules consisting of a protein core with a variable number of covalently attached carbohydrate side chains, the glycosaminoglycans (GAGs) .…”
Section: Introductionmentioning
confidence: 99%
“…Collagen, the main protein of the connective tissue is partly soluble in neutral salt solutions and swells at concentrations <1 M (Brüggemann & Lawson, 2005;Komsa-Penkova, Koynova, Kostov, & Tenchov, 1996;Russell, 1973;Winkler, 1973). Moreover, studies on cattle collagen show that the maximum solubility (Neklyudov, Berdutina, Ivankin, Mitaleva, & Evstaf'eva, 2003) is obtained at similar levels (0.8 M) as for myofibrillar proteins (Stefansson & Hultin, 1994).…”
Section: Introductionmentioning
confidence: 99%